До походження епоніму “Козак-Мамай” - Зінків, І. (Студії мистецтвознавчі, 2007)
Studying of historical sources of the Ukrainian art culture, especially its imitative factor, is impossible without wide historical context. The origin and functions of images of national painting one can retrace with the help of the oldest layers of the Ukrainian art culture, which are in national mythological and religious beliefs. Studying of these issues is very important for investigation of the origin of many images in the Ukrainian national art, especially Cossack Mamay, which is a key image of national paintings.